PEMANFAATAN TEPUNG TALAS DAN TEPUNG KACANG HIJAU DALAM PEMBUATAN FLAKES - KHAIRUNNISA KHAIRUNNISA; NOVIAR HARUN; RAHMAYUNI RAHMAYUNI (Universitas Riau, 2018)
The purpose of this research was to determine and obtain the best ratio between the taro flour and mung beanflour for making flakes. This research used a Completely Randomized Design (CRD) with 5 treatments and 3replications. The ratio of taro flour and mung bean flour 90:10, 80:20, 70:30, 60:40, and 50:50. Data werestatistically analyzed using Analysis of Variance (ANOVA) and followed by Duncan’s New Multiple RangeTest (DNMRT) test at 5% level. Results of ANOVA showed that the ratio of taro flour and mung bean floursignificantly affected moisture content, ash content, fat content, protein content, carbohydrate contents,crude fiber contents, as well descriptive and hedonic sensory test. The best treatment was the ratio of taroflour and mung bean flour 50:50 which had moisture 2.44%, ash 2.32%, fat 1.02%, protein 9.33%, carbohydrate84,44%, crude fiber content 2.97%, and durability crunchy in milk for 4.43 minutes. Overall to result ofsensory test preferred by the panelist with descriptions of slightly yellow, flavorfull taro and mung bean,mung bean test, and crunchy texture.